1993
DOI: 10.1139/x93-189
|View full text |Cite
|
Sign up to set email alerts
|

Chronology of spruce budworm outbreaks near Lake Duparquet, Abitibi region, Quebec

Abstract: The chronology of eastern spruce budworm (Choristoneurafumiferana (Clem.)) outbreaks in the vicinity of Lake Duparquet in the Abitibi region, Quebec, was determined for a period of 200 years using dendroecological methods. Growth patterns of two budworm host species, balsam fir (Abiesbalsamea (L.) Mill.) and white spruce (Piceaglauca (Moench) Voss), were compared with white cedar (Thujaoccidentalis L.), a nonhost species, and with maps of defoliation surveys. The method permitted precise dating of past outbrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
140
0
14

Year Published

1999
1999
2022
2022

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 161 publications
(158 citation statements)
references
References 0 publications
4
140
0
14
Order By: Relevance
“…We suggest that the repetitive, irregular and partial defoliation by deer also explains the asynchronism observed in stem sections from deer-affected islands, in contrasts to the synchronism observed for sections collected on deer-free islands. Thus identifying, counting and dating abrupt growth changes in salal populations should allow to reconstruct the local history of deer browsing in a way similar to what has been done using adult tree rings [26] to reconstruct the history of insect outbreaks [31,32,42] or scars to reconstruct past caribou activity [33], porcupine expansion [36], beaver occupation [4] or changes in deer population [34,35].…”
Section: Deer Effect On Growth Ratementioning
confidence: 99%
See 1 more Smart Citation
“…We suggest that the repetitive, irregular and partial defoliation by deer also explains the asynchronism observed in stem sections from deer-affected islands, in contrasts to the synchronism observed for sections collected on deer-free islands. Thus identifying, counting and dating abrupt growth changes in salal populations should allow to reconstruct the local history of deer browsing in a way similar to what has been done using adult tree rings [26] to reconstruct the history of insect outbreaks [31,32,42] or scars to reconstruct past caribou activity [33], porcupine expansion [36], beaver occupation [4] or changes in deer population [34,35].…”
Section: Deer Effect On Growth Ratementioning
confidence: 99%
“…Indeed, records of annual growth and wood density, age structure and morphological characteristics [13,25,27,43,56] are valuable signatures of past disturbances that have affected woody plants. Growth time series have been successfully used to infer spatial and temporal variations affecting several herbivore populations [31][32][33]36].…”
Section: Introductionmentioning
confidence: 99%
“…B.S.P.). A recent historical study based on tree-ring analyses have shown that the frequency of spruce budworm outbreaks has remained quite stable over the last four centuries [9], presumably because of the continuous abundance of balsam fir stands [8,24,25]. Since fir-dominated stands are still abundant and are expected to remain so into the future, sustained management of these forests must consider the impact of future insect defoliation by integrating estimation of wood losses in volume prediction models.…”
Section: Introductionmentioning
confidence: 99%
“…La standardisation permet la comparaison des arbres entre eux malgré leur différence de taille et de provenance (Swetnam et al 1985;Morin et al 1993). Elle permet aussi de diminuer les effets des facteurs autres que les épidémies qui peuvent influencer la croissance des arbres, comme l'âge de l'arbre et la situation géographique de chaque individu, en transformant les mesures de largeur de cernes en valeurs relatives (Fritts 1971(Fritts , 1976Swetnam et al 1985).…”
Section: Standardisation Des Donnéesunclassified